Behavioral adjustment in very low and normal birth weight children. - Zelkowitz, Phyllis; Papageorgiou, Apostolos; Zelazo, Philip R. (Journal of Clinical Child Psychology, 1995)
A study was conducted to examine behavioral adjustment and self-concept in very low birth weight (VLBW) children. Subjects were 52 six-year-olds and 48 nine-year-olds born at weights below 1,500 grams and a full-term control cohort matched for age, sex, and socioeconomic status. The findings indicated that VLBW children were more likely than control children to demonstrate learning problems, such as poor frustration tolerance and distractibility; to be rated as more considerate and less aggressive at age six; and to be more anxious and withdrawn at age nine. In addition, nine-year-old VLBW subjects regarded themselves as less academically competent. Among the VLBW subjects, learning problems and social and academic competence were not generally related to neonatal or demographic variables, but they were related to delays in visuomotor integration.